Role of Urdhwashakhagat Ani Marma(vital parts of the body) in Management of Tennis Elbow - Sharma, Rashi; Kumar, Sunil (International Research Journal of Ayurveda & Yoga, 2021)
Marma points are the vital points of the body. The knowledge of these Marma points constitutes an important role in Surgery. In Chinese medicine, these points are nothing but Acu points. According to both the domains of medicine, the energy is assumed to settle down at the points. Once the energy is released in the most suitable way, this aspect can certainly help to heal the person. Ani Marma is one of the delicate vital point located in extremities. Proper stimulation of upper extremity Ani Marma can provide physical and psychological relaxation and strength to the arms which is very much required in common sports injury of arms like Tennis Elbow. Basically, in Marma therapy, the focus lies on manipulating the prana or subtle energy. But, with a broader perspective, they are also effective when the person is seeking to enhance blood circulation and relieving himself from stiff muscles or sports injuries. Tennis elbow is one of the commonest sports injuries we found now a days, so it becomes necessary to explore the role of Ani Marma in Tennis Elbow. In this paper Ani Marma will be reviewed along with Tennis elbow and its role in management of tennis elbow will be explored.